THE ROLE OF OCCUPATION IN SHAPING LUXURY FASHION CONSUMERSâ BEHAVIOR: SHOPPING METHODS AND ONLINE AD PREFERENCES - Adila Khairunnisa, Ghita
In today's rapidly evolving luxury fashion industry, technology integration presents significant challenges and unparalleled opportunities. The intersection of e-commerce and digital marketing with the luxury sector is profound, and occupation plays a pivotal role in shaping consumer preferences for shopping methods and online advertisements. This research highlights how different occupations relate to consumer behavior in the luxury market, providing insights that luxury brands can leverage to refine their digital strategies. Traditionally grounded in exclusivity and craftsmanship, the luxury fashion industry is now navigating a digital transformation. As e-commerce and digital marketing become increasingly important, luxury brands must adapt to stay competitive. This study examines how occupation relates to consumer choices, focusing on online versus in-store shopping methods and preferences for online advertising. Understanding these occupational trends is essential for luxury brands aiming to enhance customer engagement and drive revenue growth. The findings indicate that different occupational groups exhibit varying shopping preferences. For instance, professionals and business owners often prefer a hybrid approach, combining online and in-store shopping experiences, while students and housewives lean towards online shopping for its convenience and accessibility. These insights suggest that luxury brands adopt an omnichannel strategy to accommodate the diverse preferences of various occupational segments. Additionally, the research shows that occupation relates to preferences for online advertisements. Business owners and entrepreneurs are more responsive to online reviews, valuing trust and credibility in their choice of luxury fashion products. In contrast, other occupational groups may prefer personalized content or influencer endorsements. Luxury brands should consider these preferences when designing their digital marketing campaigns. By exploring the relationship between occupation, shopping methods, and online advertisement preferences, this study provides a nuanced understanding of consumer behavior in the luxury fashion industry. The insights gained are critical for luxury brands seeking to tailor their marketing strategies to different occupational segments, ultimately enhancing customer satisfaction and brand loyalty.